Juridical Analysis of the Determination of Severance Pay for Employees Who Submit Resignations Based on Law No. 13 of 2003 on Employment and Law No. 11 of 20 2020 On Job Creation - Febriyanti Irzansyah; Bernat Panjaitan; Nimrot Siahaan; Risdalina Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to find out about the determination of severance pay for employees who resign based on Law No. 13 of 2003 on Manpower and Law No. 11 of 2020 on Job Creation. The method used in this study is normative juridical research method. Normative juridical research is legal research conducted by examining library materials or secondary data. In addition to using library materials, researchers also use statutory provisions related to the issues discussed in this article. The results of this study show that the determination ofseverance pay for employees who resign based on Law No. 13 of 2003 on Manpower and Law No. 11 of 2020 on Job Creation is for employees who resign are not entitled to severance pay, but the employee is entitled to reimbursement and split money as stipulated in both laws.